Constitutionality of Wiretapping by KPK in Optimization of Red-Handed Catch Operations - Irfan Amir (Al-Bayyinah, 2022)
Corruption is usually carried out in congregation and involves state administrators and/or law enforcement officers. This situation makes the Corruption Eradication Commission (KPK) often carry out Red-Handed Catch Operations/Operasi Tangkap Tangan (OTT). From these operations, the act of wiretapping has a very vital role in the success of OTT. However, KPK's steps in conducting wiretapping are sometimes disputed by various parties on the grounds that wiretapping has the potential to be misused by certain elements within KPK which can threaten a person's right to privacy and violate human rights. By relying on library research, this research is normative juridical research using qualitative descriptive data analysis techniques. The results of the study show that wiretapping is prohibited by law on the grounds of violating a person's right to privacy, but for the sake of law enforcement and eradication of corruption, wiretapping conducted by KPK is constitutional and does not conflict with Article 28D Paragraph (1) of the 1945 Constitution of the Republic of Indonesia. Privacy is not classified as a non-derogable right, KPK wiretapping is still limited and only aimed at someone who is indicated to have committed corruption.